The Manager as Mentor - Michael J. Marquardt; Peter Loan (United States of America Praeger, 2006)
One of the most valuable roles a manager can perform in today's rapidly changing environment is to mentor and inspire the people around them to learn. By nurturing talent, motivating individual development, and encouraging excellence, a manager's mentoring can enhance individual performance and the organization's prospects for success. Mentoring is not an easy skill to develop, and many managers, who may excel at leading or coaching, may be disasters as mentors when it comes to creating a bond and bringing out untapped qualities in others. The Manager as Mentor goes beyond traditional approaches to explore the newest techniques in mentoring and collaboration. Featuring personal development tools, worksheets, and references, The Manager as Mentor will enable managers to bring out the best in themselves, the people they guide, and their organizations. Mentoring is an age-old practice, tracing its roots in ancient Greek folklore to Odysseus' friend, Mentor, whom the Homeric hero entrusted as guide to his son's development. Today, with the ascendance of the knowledge age and the transformation of the workplace into an environment of continual learning, mentoring has emerged as one of the most important and valuable roles a manager can perform. By serving as a role model, providing feedback, nurturing talent, inspiring individual development, and facilitating excellence, a manager's mentoring strengthens relationships within the organization, and ultimately contributes to such critical factors as improved job performance, low turnover, and greater profitability. Mentoring is not an easy skill to attain, however, and many managers who may excel at leading teams or coordinating projects may be disasters as mentors. The Manager as Mentor explores emerging trends and approaches to help managers master the skills of effective mentoring--and enhance themselves, their proteges, and their organizations in the process. Drawing from extensive research, dozens of examples, and their own practical application in training managers around the world, the authors argue that exceptional mentoring skills can be developed. They guide the reader toward understanding the key roles that mentors play and the activities and techniques they can employ for maximum impact. Diagnostic exercises will help readers assess their strengths, weaknesses, and opportunities for development, and create a step-by-step action plan for achieving goals--either individually or in groups. The authors also offer an extensive listing of resources for more in-depth information on various aspects of mentoring, such as problem solving, active listening, and employee advocacy. Ultimately, The Manager as Mentor offers the tools by which managers can promote learning, empowerment, and insight to create vibrant organizational cultures.
Keywords: Management; Mentoring; Leadership and Mentoring (HRM2073-N)